Profil Kemampuan Pemecahan Masalah Matematika Siswa SMP pada Materi Peluang Ditinjau dari Gaya Belajar - Mufarihah, Niswatul; Yuliastuti, Rita; Nurfalah, Edy (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika (JRPIPM), 2019)
Research on profiles of mathematical problem solving ability in junior high school students on the opportunities material in terms of learning styles aimed to obtain a description of the mathematical problem solving skills based learning styles of students, that learning styles were visual, auditory, and kinesthetic. This type of research was a qualitative descriptive. The subject of research were nine students, each type of learning style consisted of 3 students. The results showed that mathematical problem solving ability of students with the type of visual learning style was superior than the students with the type of auditory and kinesthetic.